Evaluasi Kualitas Tekstur dan Rasa Macaron dengan Penambahan Minyak Atsiri Bunga Kecombrang (Etlingera Elatior) - Ocha Regita Maharani; Ita Fatkhur Romadhoni; Niken Purwidiani; Asrul Bahar (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to investigate the sensory characteristics and nutritional content of macarons with the addition of kecombrang flower essential oil (Etlingera elatior). The research was conducted to determine the effects of various concentrations of kecombrang flower essential oil (3%, 5%, and 7%) on macaron quality. The sensory attributes evaluated included color, aroma, taste, texture, and overall preference, while nutritional analysis focused on key macronutrients such as carbohydrates, sugar, fat, protein, and ash content. The sensory evaluation utilized a single-factor ANOVA and Duncan's multiple range test to compare the effects of the different concentrations of essential oil. The results indicated that the addition of 5% kecombrang essential oil yielded the most favorable sensory scores, with the highest ratings in color (4.20) and texture (4.29). Furthermore, aroma and taste were rated highly, confirming that this concentration enhanced the overall quality of the macarons. Although the likeability score did not show significant statistical differences between treatments, all treatments were generally categorized as “liked” by the panel. For the nutritional content analysis, the macaron sample with 5% essential oil was selected for testing through a proxy method. The results indicated that the macaron had a carbohydrate content of 46.31%, sugar content of 31.62%, fat content of 3.05%, protein content of 19.08%, and ash content of 0.14%. These findings are noteworthy, as the macaron with kecombrang flower essential oil showed lower carbohydrate and fat content compared to a typical macaron, while it exhibited higher protein content. These results suggest that macarons with kecombrang essential oil may offer a healthier alternative to conventional macarons, particularly for those seeking lower sugar and fat content in their diet.